Ресурсозаощаджуюча технологія фасадної кераміки із застосуванням тонких відходів вуглезбагачення - Цовма, Віталій Віталійович; Щукіна, Людмила Павлівна; Лісачук, Георгій Вікторович (НТУ "ХПІ", 2014)
Досліджена можливість зниження температури випалу фасадної кераміки з високим вмістом відходів флотації вугілля за рахунок регулювання параметрів напівсухого пресування мас. Побудовані компресійні криві ущільнення прес-порошків на основі термічно оброблених відходів вуглезбагачення. Встановлена можливість отримання лицьової цегли за ресурсозаощаджуючою технологією при температурі випалу 970 С. Запропонована технологічна схема отримання лицьової цегли з високим ступенем утилізації відходів флотації вугілля.

The possibility of reducing the firing temperature of facade ceramics with a high content of waste coal flotation by adjusting the parameters of dry-pressed masses was investigated. Compression curves constructed seal press powders based on thermally treated waste coal has been constructed. Technological parameters of manufacturing of ceramic materials have been determined: compaction pressure 110 kg/cm², humidity of press-powder 9 mass %. The possibility of obtaining face brick on the resource-saving technology at a temperature of firing 970 C was set. Materials developed by this technology have high values of performance properties: water absorption of face brick up to 12.5 %, ultimate compressive strength 37 MPa, frost resistance over 75 cycles. A flow scheme for facing bricks with a high degree of waste coal flotation was proposed.
Resource-saving technology of facade ceramics with using thin waste coal
Keywords: високовуглецеві відходи; флотація вугілля; термічна підготовка відходів; напівсухе пресування; high-carbon waste; coal flotation; heat treatment of wastes; parameters of dry pressing; facade ceramics